Human-technology relationality and self-network organization: players and avatars in World of Warcraft - Banks, Jaime, author; Martey, Rosa Mikeal, advisor; Rouner, Donna, committee member; Champ, Joseph, committee member; Aoki, Eric, committee member; Folkestad, James, committee member (Colorado State University. Libraries, 2013)
Massively multiplayer online roleplaying games, or MMOs, present an increasingly popular digital media experience whereby identity emerges as players contribute materially to play but contributions are governed by affordances and constraints of the game. Unique to this medium is the player's ability to create and control a digital body - an avatar - to represent the Self in the immersive gameworld. Although notions of identity and the Self in digital games have been examined through a number of approaches, it is still unclear how the way one sees the avatar in the uncanny situation of having two bodies - one digital, one physical - contributes to a sense of Self in and around these games. Further, it is unclear how non-human objects contribute to human senses of Self. In that vein, this study examines two research questions: How do players have relationships with their avatars in a digital game? And how does the Self emerge in relation to those relationships? Toward understanding how nonhumans play a role in the emergence of the Self, this study approaches these questions from an actor-network perspective, examining how human, nonhuman, material, and semiotic objects exist in complex webs of relations and how those relations give rise to particular senses of Self in relation to particular gameplay situations. Tracing the history of the construct of "Self" from romantic and singular to postmodern and pluralistic, I argue for an approach to Self that accommodates postmodern perspectives that embodiment is only one way that the Self is signified across spaces. Actor-Network Theory principles are integrated with postmodern notions of identity to propose a Network Model of Self. In this model, the Self is a network of personas that are, themselves, complex networks of objects. Following, I present a research approach called "object-relation mapping" that integrates phenomenology, Actor-Network Theory, social network analysis, and Grounded Theory to accommodate network structures and multiplicities of the Self as it is signified across spaces. To address the questions of how the Self emerges in relation to different player-avatar relationships, I conducted in-depth interviews with 29 players of the online digital game World of Warcraft. Transcripts of those interviews were analyzed via thematic analysis for patterns in player-avatar relationships and via object-relation mapping for semantic and structural patterns in how object-relations give rise to persona- and Self-networks. Through this analysis, a four-point typology of player-avatar relationships emerged, characterized by variations in emotional intimacy, self-differentiation, perceived agency, and primary gameplay focus. It is interpreted that the different relationships are the result of sense-making processes in response to the uncanny situation of having two bodies - one digital and one physical. Analysis revealed that players of different relationship types "activated" different types of personas, resulting in a Self that was more or less complex and consistent across game and non-game spaces. Further, players of each relationship type differently approached particular objects in crafting those personas. Ultimately a model of active Self-organization is presented, where players work with the affordances and against the constraints of objects in sense-making practices in order to maintain and protect preferred senses of agency and to achieve personal gameplay goals. These findings suggest that players see avatars as objects that are, to different degrees, both human and technological, and as resources in the purposeful organization of a Self that serves individual psychological, social, and functional purposes. Different phenomenal accounts of the player-avatar relationship emerge as players work to make sense of human-technology interactions and to maintain agency and Selfhood in the face of technological constraints. Implications for human-technology relationships, more broadly, are discussed.
Keywords: agency; video games; identity; avatars; human-computer interaction; actor-networks